Congenital adrenal hyperplasia - Miolski Jelena (University of Belgrade, Medical Faculty, 2021)
Congenital adrenal hyperplasia is a disease in which a gene mutation, which is inherited in an autosomal recessive manner, causes a disorder in the synthesis of enzymes that create glucocorticoids, mineralocorticoids, or sex steroids from adrenal cholesterol. The incidence of the classic form of the disease ranges from 1:14000 to 1:18000 births. In the majority of cases, the disease is caused by mutations in the CYP21A2 gene that participates in the synthesis of the 21 Alpha-hydroxylase. Due to the lack of enzymes, the synthesis of cortisol is blocked with the accumulation of sex hormones. The classic form of the disease, or a simple virilizing form in which patients lose salt, is diagnosed in the infant period. In the non-classical or mild form of the disease, with late-onset, patients may be asymptomatic or with a milder form of virilization postnatally. The diagnosis is made based on 17-hydroxyprogesterone levels, in order to determine the deficiency of the 21 Alpha-hydroxylase enzyme. Common complications of the disease are adrenal crisis, hypoglycemia, infertility, and premature entry into puberty. Prenatal therapy is referred to as experimental treatment, while the basis of care is hydrocortisone replacement. In severe forms of the disease, patients are unable to produce enough cortisol in response to stress from gastroenteritis, surgery, trauma, or fever, requiring higher doses of hydrocortisone. In certain cases of genital uncertainty, surgical treatment is necessary. A multidisciplinary team of experts is necessary for adequate surveillance of the disease, in both childhood and adulthood.